Gendered geographies of environmental injustice - Buckingham, Susan; Kulcur, Rakibe (Antipode, 2009)
As environmental justice concerns become more widely embedded in environmental organizations and policymaking, and increasingly the focus of academic study, the gender dimension dissolves into an exclusive focus on race/ethnicity and class/income. While grassroots campaigning activities were often dominated by women, in the more institutionalized activities of organizations dominated by salaried professionals, gender inequality is neglected as a vector of environmental injustice, and addressing this inequality is not considered a strategy for redress. This paper explores some of the reasons why this may be so, which include a lack of visibility of gendered environmental injustice; professional campaigning organizations which are themselves gender blind; institutions at a range of scales which are still structured by gender (as well as class and race) inequalities; and an intellectual academy which continues to marginalize the study of gender—and women's—inequality. The authors draw on experience of environmental activism, participant observation, and other qualitative research into the gendering of environmental activity, to first explore the constructions of scale to see how this might limit a gender-fair approach to environmental justice. Following this, the practice of “gender mainstreaming” in environmental organizations and institutions will be examined, demonstrating how this is limited in scope and fails to impact on the gendering of environmental injustice.
Keywords: approches et analyses; corps; discipline; environnement; géographie; intersectionnalité; justice environnementale; justice sociale; projet charge mentale; sciences humaines; thématiques

Genre, mouvements populaires urbains et environnement - Verschuur, Christine (Graduate Institute Publications, 2007)
Le désordre urbain et les défis environnementaux que nous connaissons ne sont pas perçus ni vécus pareillement aux Suds et aux Nords, par les femmes et les hommes, par les puissants et les exclus. Les mouvements populaires urbains et de lutte pour l'environnement participent de la réflexion sur les changements de paradigme de développement qui sont urgents et nécessaires. La perspective de genre donne des clés de lecture pour comprendre comment les asymétries féminin-masculin structurent la perception et l’organisation concrète de la vie sociale. La forte présence des femmes dans les organisations urbaines et de lutte pour l’environnement est généralement peu ou pas reconnue. Ce livre explore certains mouvements populaires urbains, qui participent au travail de prise de conscience et de revendications de droits et qui permettent ainsi d'envisager des alternatives sur des territoires de vie, sans plus attendre.
Keywords: 2000 à aujourd'hui; approches et analyses; changements climatiques; environnement; féminisme décolonial; histoire et politique; intersectionnalité; justice climatique; justice sociale; outils; ouvrages de références; projet charge mentale; périodes historiques; thématiques; écoféminisme

« Des femmes et de la territorialité » Début d’un dialogue sur la nature sexuée des droits des autochtones - Woudenberg, Gerdine Van; Lapierre, Christine (Recherches amérindiennes au Québec, 2004)
Cet article, qui se situe dans l’ensemble des discours sur les droits des autochtones, explore de façon spécifique le sujet du rapport des femmes à la territorialité. En utilisant comme étude de cas les cultures wabanakies de la côte Est, l’auteure réexamine de manière critique les documents historiques pour analyser le rapport des femmes au « lieu » à travers leur relation à leur environnement et elle étudie comment le contexte de cette relation a été transformé par les processus de colonisation. Puisque ce texte s’insère dans le large champ des discours sur les droits autochtones, il soulève des questions importantes sur la position des femmes autochtones dans les processus actuels de reconnaissance des droits et des titres, non seulement comme participantes actuelles mais aussi comme acteurs historiques.
Keywords: 1600-1699; 1700-1799; 1800-1899; 1900-1999; 2000 à aujourd'hui; 2000-2009; amériques; anthropologie; approches et analyses; canada; cours; discipline; droits des femmes*; droits des femmes* autochtones; environnement; histoire et politique; intersectionnalité; justice sociale; pol4105; premier cycle; périodes historiques; régions géographiques; sciences humaines; sexisme; système colonial; systèmes d'oppressions; territoire; thématiques; wabanakie

Feminism and the body - Schiebinger, Londa (Oxford readings in feminism, 2000)
This exciting new Handbook offers a comprehensive overview of the contemporary state of the field. The editors’ introduction and forty-five essays cover feminist critical engagements with philosophy and adjacent scholarly fields, as well as feminist approaches to current debates and crises across the world. Authors cover topics ranging from the ways in which feminist philosophy attends to other systems of oppression, and the gendered, racialized, and classed assumptions embedded in philosophical concepts, to feminist perspectives on prominent subfields of philosophy. The first section contains chapters that explore feminist philosophical engagement with mainstream and marginalized histories and traditions, while the second section parses feminist philosophy’s contributions to with numerous philosophical subfields, for example metaphysics and bioethics. A third section explores what feminist philosophy can illuminate about crucial moral and political issues of identity, gender, the body, autonomy, prisons, among numerous others. The Handbook concludes with the field’s engagement with other theories and movements, including trans studies, queer theory, critical race, theory, postcolonial theory, and decolonial theory. The volume provides a rigorous but accessible resource for students and scholars who are interested in feminist philosophy, and how feminist philosophers situate their work in relation to the philosophical mainstream and other disciplines. Above all it aims to showcase the rich diversity of subject matter, approach, and method among feminist philosophers.
Keywords: LGBTQIA2+; afro-féminisme; approches et analyses; corps; cours; discipline; environnement; féminisme autochtone; féminisme décolonial; histoire et politique; identités LGBTQIA2+; incontournable; intersectionnalité; lit4700; oui; philosophie; postmodernisme; premier cycle; queer; ressource en ligne; sciences humaines; thématiques; transféminisme